Cardiovascular fitness in late adolescent males and later risk of serious non-affective mental disorders: a prospective, population-based study. Issue 3 (28th June 2017) - Nyberg, J.; Henriksson, M.; Åberg, M. A. I.; Rosengren, A.; Söderberg, M.; Åberg, N. D.; Kuhn, H. G.; Waern, M.
Abstract : Background: Cardiovascular fitness in late adolescence is associated with future risk of depression. Relationships with other mental disorders need elucidation. This study investigated whether fitness in late adolescence is associated with future risk of serious non-affective mental disorders. Further, we examined how having an affected brother might impact the relationship. Method: Prospective, population-based cohort study of 1 109 786 Swedish male conscripts with no history of mental illness, who underwent conscription examinations at age 18 between 1968 and 2005. Cardiovascular fitness was objectively measured at conscription using a bicycle ergometer test. During the follow-up (3–42 years), incident cases of serious non-affective mental disorders (schizophrenia and schizophrenia-like disorders, other psychotic disorders and neurotic, stress-related and somatoform disorders) were identified through the Swedish National Hospital Discharge Register. Cox proportional hazards models were used to assess the influence of cardiovascular fitness at conscription and risk of serious non-affective mental disorders later in life. Results: Low fitness was associated with increased risk for schizophrenia and schizophrenia-like disorders [hazard ratio (HR) 1.44, 95% confidence interval (CI) 1.29–1.61], other psychotic disorders (HR 1.41, 95% CI 1.27–1.56), and neurotic or stress-related and somatoform disorders (HR 1.45, 95% CI 1.37–1.54). Relationships persisted in models that included illness in brothers. Conclusions: Lower fitness in late adolescent males is associated with increased risk of serious non-affective mental disorders in adulthood.